Analisis Penyediaan Air Bersih di Gedung Rektorat Universitas Tanjungpura - Erwanda, Ery; Umar, Umar; Gunarto, Danang (Universitas Tanjungpura, 2024)
The provision of clean water in the Tanjungpura University Rectorate Building area until now has not been analyzed for its efficiency leve. In this research, 11 buildings including the Tanjungpura University Rectorate Building were reviewed. Therefore, it is very important to analyze whether the water available in these buildings is still sufficient, given that the need for clean water will continue to change from time to time. In this final research, clean water demand for the Tanjungpura University Rectorate Building area in 2023 is predicted, and clean water usage data is taken for 1 month of working days from March to April 2023. Tanjungpura University Rectorate Building Area itself has a total of 11 buildings with 2 types of areas, namely office areas and education areas. The results of observations of 5 meters in the Tanjungpura University Rectorate Building Area that the amount of clean water usage is 688.9 m3 / month. Then the analysis of clean water demand in the Tanjungpura University Rectorate Building Area is carried out both based on the building area and the total number of clean water users in the area. The results of this study found that the effectiveness of each area is known to be different, but in total, the amount of clean water usage is smaller than the predicted amount of clean water demand. So it can be concluded that the provision of clean water in the Tanjungpura University Rectorate Building area in 2023 is effective.